Formação do conceito de função a partir da lógica matemática fundamentada na teoria de formação por etapas das ações mentais de Galperin nos estudantes do 1º Ano do Ensino Médio - Sindeaux, Eduardo Ribeiro (2015)
This work contributes to an improvement in the Mathematics teaching and learning using the mathematical logic as a forerunner tool in the development of the mathematical reasoning through the Theory of Formation by Phases of Galperin’s Mental Actions in the formulation of the concept of function through essential properties presented during the text and the activity of the problem situation (ASP), attending to the prerogatives of the PCN’s and National Council of Education. It works with the contents of the mathematical logic, sets and functions in a formal language way, but aiming the students of the first grade in the high school. The proposal of an oriented guiding base of the type 3 action that is widespread, complete and elaborated independently, lesson and teaching plan according to a didactic to the teaching of the concept of function solidify the assimilation of knowledge. So this work helps in the comprehension of the concept of function contributing to the intellectual and cognitive development of the student.